Il sistema sociale dell’assenza organizzata di pace e la violenza strutturale. Punto di partenza, soggetto e compiti di una Pedagogia critica della Pace - Bernhard, Amin (Studi sulla Formazione/Open Journal of Education, 2019)
The pedagogy of peace should fight against the “social structures of discord”: the article addresses this issue and invites to conceive the pedagogy of peace as a “pedagogy of resistence” against the organized discord. Critical pedagogy has a key role in this task because it should understand the inability of the current society to build peace.